Ireland : Selected Issues and Statistical Appendix. (IMF Staff Country Reports; Country Report, 2000)
The sharp and sustained increase in Ireland's housing prices well in excess of income growth, together with rapidly declining affordability for new house buyers, raises concerns that expectations-led demand may have resulted in housing prices overshooting their sustainable levels. The paper reviews the main factors behind the improvement in Ireland's economic performance, and alternative assessments of the stance of fiscal policy during a period of rapidly accelerating economic growth. The major factors that are likely to influence fiscal policy are also reviewed.